Effects of spatial exercises on students' visuo-spatial aptitude, problem-solving ability, and attitude towards geometry - Belarga, Alona Matulac
Many researchers acknowledge that visuo-spatial aptitude is related to mathematical ability. the extent to which this aptitude can be enhanced and its effects on mathematics problem-solving ability and attitude were the concerns of this study. This research sought to find out whether students exposed to spatial exercises would differ from students not exposed the same in visuo-spatial aptitude, problem-solving ability and in their attitudes towards geometry. The study also looked into the factors correlated to spatial ability and the hierarchy of spatial skills. The subjects of the study consisted of 94 third year students in West Visayas State University, Secondary Laboratory School in school year 1994-1995. They were matched on the basis of Mathematics II general average, and then randomly assigned to the control and experimental groups. Both groups had the same number of male and female students. Visuo-spatial Aptitude Test, Problem-Solving Ability Test, A Geometry Attitude Inventory and Home Environment Questionnaire were used for collecting data. The instruments were subjected to validity and reliability analysis and were found to be highly reliable. The first three instruments were given as pretests and posttests. The experimental period lasted for 8 1/2 weeks. All experimental were the same for both groups. Twenty-four (24) exercises for developing visuo-spatial awareness were given once a day, except during scheduled weekly quiz. Frequencies and descriptive statistics were used to describe the sample. To test the significance of the difference between means, t-test for paired samples was used in comparing the two groups. Pearson r was used to determine the relationship among the variables studied. To find out if spatial skills are hierarchical in nature. Guttman Scalogram Analysis was used. The study found the following: 1) The two groups were initially comparable in mathematical capacity, visuo-spatial aptitude, problem-solving ability and in their attitudes towards geometry. After the treatment, the experimental group scored higher in visuo-spatial aptitude and problem-solving ability. No difference was noted in their attitudes towards geometry. 2) Visuo-spatial aptitude is positively and significantly correlated to problem-solving ability, frequency of reading or journals, playing of computers games with friends, eating together as a family, yearly income, having puzzles at home and family 's active involvement in activities; but negatively correlated to appreciating child's effort in making good in his school subjects. 3) The perceptual skills are hierarchical. Students are more familiar with matching the parts to the target figure, if the figures are squares, rhombi, or circles rather than triangles, trapezoids, pentagons or heptagons. The skill of matching the parts to the target figure is easiest when the given parts have similar characteristics as the intact target figure and the parts contain congruent and/ or similar figures. The study concludes that giving of visuo-spatial exercises improves visuo-spatial aptitude and problem-solving ability. However, the exercises are not able to significantly improve the students' attitude toward geometry. Problem-solving ability, frequency of reading magazines or journals, playing of computer games with friends togetherness, yearly income, having puzzles at home, parents' appreciation of the child's effort in making good in his school subjects, and family involvement in activities are significant correlates of visuo-spatial aptitude. Spatial skills are hierarchical. Lowest in hierarchy of difficulty are squares, followed by rhombi and circles. Next are triangles and other polygons. Based on the findings and conclusions, it is recommended that the schools and the homes structure experience to accommodate non-verbal modes of learning, encourage the children to read wholesome magazines and journals more often, allow the children to do activities that develop spatial skills with his peers. Family must actively engage together in activity. Studies on the hierarchy of other visuo-spatial skill (including nongeometric concepts) are also recommended.